2015
DOI: 10.1177/1468796815581428
|View full text |Cite
|
Sign up to set email alerts
|

‘Not everyone’s gonna like me’: Accounting for race and racism in sex and dating web services for gay and bisexual men

Abstract: Sexual racism can be thought of as a specific form of racial prejudice enacted in the context of sex and dating. It is a contentious issue among gay and bisexual men looking for partners online. This study draws upon 14 in-depth interviews conducted between August and October 2012 with gay and bisexual men of colour in Australia. Data were thematically analysed to identify interpretations and experiences of, and reactions to sexual racism online. Understandings of online sexual racism were diverse, ranging fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 36 publications
4
46
0
5
Order By: Relevance
“…Indeed, McGregor (Verass, 2016) explained that it is common practice for Grindr users to express a sexual preference and that often profiles will include statements such as ‘no rice or spice’, or ‘Euros only’, ‘Aussie only’, ‘GWM [gay white men] only’ (Donelly, 2016; Rafalow et al, 2017). Likewise, in an Australia-wide online survey of gay and bisexual men on the topic of sexual preference conducted in 2016, it was revealed that many of the respondents discriminated among partners on the basis of race (Callander et al, 2016). The results revealed that Aboriginal men were deemed less attractive than most other categories, including white men, and that they would most likely be romantically or sexually excluded on the basis of race.…”
Section: Findings 2: ‘Sexual Racism’ On Grindrmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, McGregor (Verass, 2016) explained that it is common practice for Grindr users to express a sexual preference and that often profiles will include statements such as ‘no rice or spice’, or ‘Euros only’, ‘Aussie only’, ‘GWM [gay white men] only’ (Donelly, 2016; Rafalow et al, 2017). Likewise, in an Australia-wide online survey of gay and bisexual men on the topic of sexual preference conducted in 2016, it was revealed that many of the respondents discriminated among partners on the basis of race (Callander et al, 2016). The results revealed that Aboriginal men were deemed less attractive than most other categories, including white men, and that they would most likely be romantically or sexually excluded on the basis of race.…”
Section: Findings 2: ‘Sexual Racism’ On Grindrmentioning
confidence: 99%
“…This issue of ‘sexual preference’ and ‘racial exclusion’ is regularly referred to as ‘sexual racism’ (Bedi, 2015; Callander et al, 2016; Robinson and Frost, 2018). Some however, argue that it is ‘sexual freedom and individual preferences’ as opposed to racism (Callander et al, 2016: 4).…”
Section: Findings 2: ‘Sexual Racism’ On Grindrmentioning
confidence: 99%
See 1 more Smart Citation
“…While interesting, it is not very surprising given that race has always played a critical role in the construction of desire and desirability (Nagel 2003). In fact, desire for whiteness has been noted by a number of scholars examining race and racism in the gay community (Callander, Holt and Newman 2016; Han 2007; Robinson 2015; McBride 2005; Teunis 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of empirical work documents racial discrimination among gay and bisexual users of online platforms in particular. 2 This research describes the many ways in which discrimination reinforces racial stereotypes, hierarchies, and social distance (e.g., [16,72]; see [5] for further review).…”
Section: Intimate Inequities Onlinementioning
confidence: 99%